Factors Affecting the Uptake of Non Communicable Disease Screening Service: A Multiple Logistic Regression in Kapuas Hulu, West Kalimantan - Riza Firdaus; Yulia Lanti Retno Dewi; Bhisma Murti (Masters Program in Public Health, 2019)
Background: A non-communicable disease is the leading cause of mortality in the world. It is also a serious threat to health in low- and middle-income countries. Prevention efforts can be carried out through early detection and monitoring the risk factors of non-communicable disease. This study aimed to determine the factors affecting the uptake of non-communicable disease screening at integrated guidance post in Kapuas Hulu, West Kalimantan.Subjects and Method: This was a cross sectional study. This study was conducted in Kapuas Hulu, West Kalimantan from August to October 2019. There were 200 people as the sample of the study. They were selected by fixed disease sampling. The dependent variable was the uptake of non-communicable disease screening. The independent variables were subjective norm, health information exposure, family support, cadre support, healthy behavior, health status, attitude, intention, and type of integrated guidance post. The data were collected by using questionnaires. They were analyzed by a multiple logistic regression with Stata 13.Results: The uptake of non-communicable disease screening increased with subjective norm that supported (OR=2.86; 95%CI=1.16 to 7.01; p=0.022), lots of health information exposure (OR= 2.64; 95%CI=1.08 to 6.46; p=0.033), strong family support (OR=3.06; 95%CI=1.28 to 7.33; p= 0.012), strong cadre support (OR=2.75; 95%CI=1.15 to 6.54; p=0.022), positive healthy behavior (OR= 2.82; 95%CI=1.20 to 6.60; p=0.017), health status of having non-communicable disease